Correlation between Teacher’s PCK (Pedagogical Content Knowledge) and Student’s Motivation in Primary School - Maryani, Ika; Martaningsih, Sri Tutur (International Journal of Evaluation and Research in Education (IJERE), 2015)
Various learning problems occur due to the teachers’ inability in managing the learning process. Teacher’s learning skill is influenced by their understanding in the curriculum components which are including pedagogical knowledge and content knowledge. The aims of this research were to determine: 1) the condition of Pedagogical Content Knowledge (PCK) of primary school teachers; and 2) the relationship between the teacher’s PCK with student’s motivation in learning. The experiment was conducted on teachers and primary school students in Yogyakarta, Indonesia. Teacher samples were taken by purposive sampling technique, whereas the student samples were taken by random sampling technique. The data of students’ motivation were collected through questionnaire, whereas data of PCK obtained from the results of teachers’ competency test in the last 2013. Data were analyzed using Pearson correlation technique. The results showed there is a relationship between teacher’s pedagogical content knowledge with student motivation in learning (p value is 0.000, and r is 0.0907).